The Activity Antihiperglikemi Fraksi- fraksi Extract Ethanol Leaves Sembung (Blumea Balsamifera (L. ) DC) in Rats Induced Streptozotozin Nikotinamid - Joseph Billi; Mawaqit Makani (Indonesian Journal of Global Health Research, 2024)
Diabetes mellitus (DM endokrinologis) is a disease or abnormality metabolic disorder is a group of heterogeneous where impaired insulin secretion can cause high blood glucose levels (abnormal settled) and glucose intolerance. It is characterized by abnormally high blood sugar (hiperglikemia). Hiperglikemia is a situation where patients fasting blood sugar levels rose above 110 mg / dl blood sugar levels and 2 hours after eating (PP) above 140 mg / dl. The discovery of herbal ingredients for antihyperglycemia is very necessary because diabetes is one of the most common diseases in the world. Blumea balsamifera leaf extract (BBLE) is known to be able to lower blood sugar levels because it has metabolite compounds that play a role in lowering blood sugar levels. Objective to evaluate the antihyperglycemic activity of ethanol extract and various fractions of sembung leaves (Blumea balsamifera) against streptozotocin-nicotinamide-induced rats. Method: This study used a randomized post-test only control group. Extraction was carried out using ethanol, then evaporated. Fractionation was carried out using the liquid-liquid extraction method, using water, ethyl acetate and n-hexane as solvents. For 10 days, 30 male Wistar rats were adapted, then their blood sugar levels were measured 2 hours after measuring their blood sugar levels, the test animals were given stz-na then left for 2 weeks after being given stz-na, when the blood sugar levels of the test animals were above 200 then given ethanol extract, water fraction, ethyl acetate fraction, n-hexane fraction and glibenclamide as positive controls and observed for 2 weeks until the blood sugar levels of the test animals could return to normal or below 200. Ethanol extract, n-hexane fraction, ethyl acetate fraction, water fraction and positive control are able to reduce blood sugar levels as seen from the following percentage reduction extract of 47.46 on day 17 and percentage reduction on day 24 of 75.62. n-hexane fraction of 46.19 on day 17 and percentage reduction on day 24 of 74.22. Ethyl acetate fraction of 51.22 on day 17 and percentage reduction on day 24 of 82.47. Water fraction of 56.46 on day 17 and percentage reduction on day 24 of 84.48. Positive control (glibenclamide) of 54.85 on day 17 and percentage reduction on day 24 of 83.17. Ethanol extract and fractions of sembung leaves (Blumea balsamifera (L.) DC) have antihyperglycemic activity against streptozotocin-nicotinamide-induced mice, and the best in reducing blood sugar levels in mice is the water fraction group followed by positive control and the next sequence is the ethyl acetate